KEBIJAKAN KRIMINAL TERHADAP PERLINDUNGAN TERHADAP ANAK DI BAWAH UMUR YANG IKUT IBUNYA MENJALANI HUKUMAN DI LEMBAGA PEMASYARAKATAN (LAPAS) PEREMPUAN - Mompang L. Pangabean; Hendry J. Pandiagan; Sariyanti T. S. Siahaan (Fakultas Hukum Universitas Kristen Indonesia, 2021)
This thesis discusses the criminal policy towards the protection of minors who accompany their mothers to serve their sentences in the Women's Penitentiary. Through a literature study using an empirical legal approach, it is concluded that the implementation of the protection of minors who participate in their mothers are serving sentences at the Class IIA Women's Penitentiary in Pontianak and the Class III Manokwari Women's Penitentiary so far refers to the provisions of Article 20 paragraph (3) and paragraph (4) Government Regulation No. 32/1999 concerning Terms and Procedures for the Implementation of the Rights of Correctional Assistants. Referring to the provisions of Article 20 paragraph (3) and paragraph (4) of Government Regulation Number 32 of 1999 concerning Requirements and Procedures for the Implementation of the Rights of Correctional Assistants, the form of protection for minors who are accompanying their mothers undergoing sentences in Women's Penitentiary is limited to the provision of even then additional food on the doctor's instructions. Meanwhile, the issue of placing minors who accompany their mothers to serve their sentences in Women's Penitentiary is not regulated in statutory regulations. The reasons for underage children whose mothers are serving sentences in Women's Penitentiary have not received protection, among others are as follows: (a) Factors of legal/regulatory rules; and (b) Facility and infrastructure factors. The criminal policy towards the protection of minors who accompany their mothers to serve their sentences in a Women's Penitentiary must consider the legal interests as well as the interests of the child. The criminal policy against the protection of minors who participate in their mothers serving sentences in a Women's Penitentiary must be implemented for the following reasons: (a) Children need special protection and care for the physical and mental reasons of minors and mature so that it must be legally protected; (b) The state is obliged to protect the rights of children from birth as stated in the basis of the constitution, this means that the state is also obliged to protect the rights of minors (toddlers) who accompany their mothers to serve a sentence in a Women's Penitentiary. Moreover, the LAPAS environment is not a good environment or place for children, because it will adversely affect the mental development of the child; and (c) There are no regulations that specifically regulate the issue of protection of minors who accompany their mothers to serve their sentences in the Women's Penitentiary. Indeed, the Government has issued Law Number 23 Year 2002 jo. Law Number 35 of 2014 concerning Child Protection, however, in the Child Protection Law does not regulate the issue of protection for minors who accompany their mothers serving sentences at Women's Penitentiary. Keywords: Criminal Policy, Protection, Minors, Women's Penitentiary